EP136/#823 Aberrant beta-catenin distribution as potential prognostic biomarker in endometrial cancer. (4th December 2022) - Moon, Ashley S; Beshar, Isabel; Jennings, Kj; Howitt, Brooke; Renz, Malte
Abstract : Objectives: Based on the TCGA results for endometrial cancer, aberrant beta-catenin distribution may be a predictive biomarker for recurrence in early stage, low grade endometrioid endometrial cancer. Methods: This retrospective single institution cohort study reviewed 316 patients with endometrial cancer from 2017 to 2021. Uterine serous, carcinosarcoma, clear cell endometrial histologies were excluded. Stage, FIGO grade, beta-catenin status by immunohistochemistry (aberrant nuclear distribution vs. wild-type plasma membrane distribution), recurrence status (local vs. distant) were obtained from the medical records. Stage was classified as early (stage IA/IB) or advanced (stage II/IIIA/IIIB/IIIC/IVB). X2 test, Fisher test, and logistic regressions were performed. Results: 213 patients were included. The majority had stage IA (50.0%, n=106) or FIGO grade I disease (69.8%, n=148). Recurrences were observed in 40 patients (18.9%) vs. no recurrences in 172 patients (81.3%). Recurrences did not correlate with beta catenin distribution: 20% (n=19) of aberrant beta-catenin recurred vs. 17.9% (n=21) of wild-type beta-catenin recurred (p=0.70). Local and distant recurrences did not vary significantly by beta-catenin status (p=0.36). Most recurrences occurred in the vaginal cuff (37.50%, n=15), followed by lung (17.50%, n=7). The odds ratio (OR) for beta-catenin aberrant distribution on recurrence risk was non-significant at 1.17 (0.59, 2.32). In a sensitivity analysis of early-stage, low-grade patients (n=109), recurrence also did not vary significantly by beta-catenin distribution (p=0.64). Conclusions: Aberrant beta-catenin distribution did not significantly correlate with recurrence in early stage, low grade endometrioid uterine cancer. Further research is warranted to evaluate the effect of aberrant beta-catenin distribution on endometrial cancer prognosis.